Diffusion brazing of a gamma-TiAl Alloy Using Tini 67: microstructural evolution of the interface - Guedes, A. (2008)
A detail study focussing the microstructural evolution of the interfacial zone in the course of the processing of Ti-47Al-2Cr-2Nb joints using Tini 67 as filler alloy was carried out in this investigation. Experiments, aiming the understanding of the mechanisms that promote the melting of the braze alloy, were performed below the solidus temperature of the filler, at 750 and 900 degrees C. Diffusion brazed samples were joined at 1000 and 1100 degrees C, with no dwelling stage and subsequently quenched in water in order to frozen the microstructure formed at the bonding temperature. The interfaces were analysed by scanning electron microscopy (SEM) and by energy dispersive X-ray spectroscopy (EDS), respectively. In the course of the heating stage, several single phase layers were formed within the filler alloy due to the solid state interdiffusion of Ti and Ni atoms. At 900 degrees C, the microstructure of the filler evolved form the initial Ti(alpha)/(Ni)/Ti/(alpha) layers to a Ti(beta)/Ti2Ni/TiNi/TiNi3/TiNi/Ti2Ni/Ti (beta) layered microstructure. The filler alloy begun to melt due to the eutectic reaction between the contiguous layers composed of Ti(beta) and Ti2Ti. After joining, the main phases detected at the interfaces were alpha(2)-Ti3Al, Ti-Ni-Al and Ti-Ni intermetallics. For joining at 1000 degrees C, a substantial amount of residual filler (Ti2Ni and Ti (alpha) particles) was also detected at the central zone of the interface. No marked evidences of residual filler zones were noticed for joining at 1100 degrees C, a substantial amount of residual filler (Ti2Ni and Ti (alpha) particles) was also detected at the central zone of the interface. No marked evidences of residual filler zones were noticed for joining at 1100 degrees C; instead, a mixture alpha(2)-Ti3Al with Ti-Ni-Al or Ti2Ni intermetallics was detected at the centre of the interface.